Acute kidney injury in neonatal age - Giovanni Ottonello; Angelica Dessì; Paola Neroni; Maria Elisabetta Trudu; Danila Manus; Vassilios Fanos (Hygeia Press di Corridori Marinella, 2014)
Acute kidney injury (AKI) is a pathology characterized by a sudden decrease in kidney function that results in the accumulation of nitrogenous waste products and alteration of the regulation of extracellular fluid volume, electrolytes, and acid-base homeostasis. Previously known as acute renal failure (ARF), in the most recent classifications the term "failure" is used only in conditions requiring renal replacement therapy, peritoneal dialysis or hemodialysis. The diagnosis and therapy of AKI, especially in the neonatal period, still present great difficulties and are the subject of ongoing research in the attempt to improve the prognosis of a pathology still featuring high rates of morbidity and mortality.   Proceedings of the International Course on Perinatal Pathology (part of the 10th International Workshop on Neonatology · October 22nd-25th, 2014) · Cagliari (Italy) · October 25th, 2014 · The role of the clinical pathological dialogue in problem solving Guest Editors: Gavino Faa, Vassilios Fanos, Peter Van Eyken